Total quality management - Naidu, N. V. R.; Babu, K. M.; Rajendra, G. (New Delhi : New Age International, 2006)
This book covers all aspects of Total Quality Management(TQM). It provides not only the principles and practices but also the Tools and Techniques. It ensures the reader to have a sound understanding of all the concepts of TQM.
Cover -- Copyright -- Dedication -- Preface -- Contents -- Chapter 1 Quality and Quality Control -- Inspection13; -- Quality Characteristics13; -- Chapter 2 Probability Distributions -- Introduction13; -- Probability13; -- Binomial Distribution13; -- Poisson Distribution13; -- Normal Approximation to the Binomial13; -- Chapter 3 An Overview of Total Quality Management -- Evolution of Quality13; -- Definition13; -- TQM Concepts13; -- Basic Approach13; -- The Deming's Philosophy13; -- Gurus of Total Quality Management13; -- The Five Principles of TQM13; -- History of Quality Control in India13; -- TQM Organization13; -- Chapter 4 Leadership -- Introduction13; -- Characteristics of Quality Leaders13; -- Role of TQM Leadership13; -- Continuation Process Improvement13; -- The PDSA Cycle13; -- Six Sigma(6o) Quality13; -- Conclusion13; -- Chapter 5 Tool and Techniques of TQM -- Introduction13; -- Benchmarking and Competitive Analysis13; -- Quality by Design13; -- Chapter 6 Statistical Process Control -- Introduction13; -- TQC Tools13; -- Process Capability13; -- Summary13; -- Chapter 7 Control Charts for Attributes -- Attribute Control Charts13; -- p-Chart 13; -- np-Chart13; -- C-Chart or U-Chart13; -- Chapter 8 Acceptance Sampling -- Introduction13; -- Types of Sampling Plans13; -- Operating Characteristic Curve (O.C. Curve)13; -- Double Sampling Plan13; -- Chapter 9 Reliability -- Definition13; -- Redundancy13; -- Chapter 10 Experimental Design -- Introduction to Design of Experiments13; -- Terminology Used in Design of Experiments13; -- Some Important Designs13; -- Quality Control13; -- Taguchi's Quality Philosophy 13; -- Parameter Design13; -- Tolerance Design13; -- Statistical Quality Control Tables -- Binomial Distribution13; -- Poisson Distribution13; -- Normal Curve13; -- t Distribution13; -- Chi-Square Distribution13; -- F Distribution13; -- Random Numbers13; -- Factors for Computing 3963; Control Limits13.
Includes bibliographical references.
Print version record.
Keywords: Total quality management; Quality control; BUSINESS & ECONOMICS -- Quality Control; BUSINESS & ECONOMICS -- Total Quality Management; Quality control; Total quality management; Electronic books; Electronic books